The correlation of anthropometric variables and jump power performance in elite karate athletes - Spigolon, D.; Hartz, C. S.; Junqueira, C. M.; Longo, A. R.; Tavares, V.; Fayçal, H.; Paula, M.; Jacinto, L. C.; Moreno, M. A. (Journal of Exercise Physiology online, 2018)
The purpose of this study was to evaluate the relationship between the anthropometric variables and the power jump capacity in elite athletes of the Karate modality. Fifty-one elite Karate athletes from both genders (22 ± 5 yrs old) performed two evaluations: (a) Anthropometric variables that were used to obtain body composition; and (b) Vertical jumps tests to quantify jump power. For analysis of the relationship between the variables, Pearson Linear Correlation Coefficient was used. The findings indicate that there was a low but significant correlation between weight and power of the jump, a high significant inverse correlation between percentage of body fat and power of the jump, and a moderate significant correlation between fat free mass and power of the jump. These findings suggest that body composition presents an influence on the athletes' capacity of power jump, and it can be used as a tool to guide the technical aspects of the training process to help improve karate performance.